Psychometric evidence of the Peruvian version of the Patient Health Questionnaire, PHQ-9 - Quispilcaya Capcha, Kennedy (2025)
The objective of this study was to analyze the psychometric properties of the Peruvian version of the Patient Health Questionnaire (PHQ-9), with a sample of 33,613 people, obtained from a database of the ENDES 2019. The methodology is basic level, not experimental and instrumental design. The results indicate good quality of the items, showing the ability to measure the same construct and differentiate people with different levels of depression. A two-dimensional factor (somatic and cognitive) model, with adequate goodness of fit was identified (RMSEA = .097; CFI = .932; NFI = .932; TLI = .906). Finally, a high level of reliability was obtained (ω = .892).